Bowel cleansing effectiveness and safety of 1L PEG + Asc in the real-world setting: Observational, retrospective, multicenter study of over 13000 patients - López-Jamar, José Miguel Esteban; Gorjão, Ricardo; Cotter, José; Lorenzo-Zúñiga García, Vicente; Pantaleón Sánchez, Miguel Angel; Carral Martínez, David; Sábado, Fernando; Pérez Arellano, Elena; Gómez Rodríguez, Blas José; López Cano, Antonio; Machlab, Salvador; Arieira, Cátia; Akriche, Fatma; Turbí Disla, Carmen; Rodriguez Muñoz, Sarbelio (Endoscopy International Open, 2023)
Background and study aims Effective bowel cleansing is critical for detecting lesions during colonoscopy, highlighting the importance of bowel preparations. 1L polyethylene glycol (PEG) + ascorbate (Asc) is the only recommended 1L PEG product in Europe and the United States. Its efficacy was demonstrated in large-scale controlled trials and confirmed in smaller-scale real-world studies. However, no large-scale real-world data exist.Patients and methods This observational, retrospective, multicenter study, used outpatient follow-up data from medical records from 10 centers in Spain and two in Portugal. Outpatients aged ≥18 years using 1L PEG + Asc as bowel preparation were included. The main outcome measures were overall adequate colon cleansing (Boston Bowel Preparation Scale [BBPS] score ≥6 with BBPS score ≥2 in each segment) and high-quality cleansing of the right colon (BBPS score=3).Results Data from 13169 eligible patients were included. Overall cleansing success was achieved in 89.3% (95%CI 88.7%-89.8%) and high-quality cleansing in the right colon in 49.3% (95%CI 48.4%–50.2%) of patients. For the overnight split-dose and same-day regimens, overall adequate quality cleansing success rate was 94.7% and 86.7% (P<0.0001) and high-quality cleansing of the right colon rate was 65.4% and 41.4% (P<0.0001), respectively. Colonoscopy was completed in 97.3% of patients, with non-completion due to poor preparation in only 0.8%; 2.3% of patients experienced at least one adverse event (AE).Conclusions This large-scale, real-world study demonstrates the effectiveness of 1L PEG + Asc in the total and right colon, with a low percentage of patients with AEs in routine clinical practice.
Keywords: Colonoscopy; NER1006; Plenvu; Polyethylene glycol; bowel preparation